Implementasi STBI “Search Operation” dalam Meningkatkan Literasi Informasi Mahasiswa dalam Pembelajaran Daring - Ratih Desnita Wilanda (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2021)
Information literacy ability is very important possessed by students. It is intended that the information needed can be met properly. This article will discuss the implementation of the STBI